Implementasi Peraturan Daerah Kabupaten Klaten Nomor 28 Tahun 2018 tentang Perlindungan Anak Terhadap Anak Yatim Piatu Akibat Covid-19 di Kabupaten Klaten - Danendra, Muhammad Ichsan; Achmad, , (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
This research aimed to find out about how the implementation of Klaten Regency Regional Regulation No. 28 of 2018 on Child Protection of orphans due to Covid-19 in Klaten Regency, especially in fulfillment of basic needs such as health, education, and food, also how the obstacles experienced by the Klaten Regency Government in providing protection to orphans due to Covid-19. This research was empirical legal research and descriptive research with a qualitative approach. The types and sources of data used in this study include primary data was obtained in several services included the Social Service of Women Empowerment and Child Protection, Population Control and Family Planning, and the Education Office and also the secondary data. From the results of this research, it can be concluded that the provision of protection for orphans, Covid-19 related to the implementation of Klaten Regency Regional Regulation No. 28 of 2018 on Child Protection has been guaranteed its basic rights. These rights included educational, health, and food needs. The obstacles experienced by the Klaten Regency Government in providing protection for due to Covid-19 include the communication flow between stakeholders in providing protection for these children is too long, the target group has diverse backgrounds, as well as the socio-economic conditions of the group target comes from vulnerable families.